Le rapport au savoir en Anthropocène entre problématisation et coopération - Cécile Redondo; Mathieu Ferrand; Éric Mutabazi; Renaud Hétier; Nathanaël Wallenhorst (Éducation et Socialisation)
The Anthropocene event (Bonneuil & Fressoz, 2016), through the scale and urgency of its effects, disrupts our ability to live together in a habitable world. The threat is twofold: it weighs not only on life itself but also on democracy. On this latter point, authoritarianism and illiberalism may appear more efficient than democratic debate (and its frequent indecision). Yet formal education requires time—a long time—especially to allow learners to engage in problematization and the construction of problems, rather than receiving immediate truths. In the face of the complex problem that is the Anthropocene, the challenge is to develop a didactics of inquiry and a genuine co-construction between teachers and students. The example of Freinet pedagogy will thus be described and analyzed according to the specific requirements of problematization, in order to meet the challenge of education in the Anthropocene.